’Mil rochas e tal...!’: inventário dos sítios da arte rupestre do Vale do Côa - Reis, Mário (Portvgalia : Revista de Arqueologia do Departamento de Ciências e Técnicas do Património da FLUP, 2018)
Since its discovery, and from its public announcement in late 1994, the rock art of the Côa valley has not ceased to increase its numbers, which are reflected at this point in more than 70 sites, with a quantity of engraved rocks that now exceeds one thousand records. In parallel, the diversity of these sites and records has also increased remarkably. This paper presents a description of each site of the Côa rock art, pointing out its topographical features, the history of the evolution of the discoveries and the current state of archaeological survey, the quantity and chronology of the known records and their characteristics, highlighting the main rocks and motifs.